Human impact on atmospheric composition - Kanakidou Maria (EPJ Web of Conferences, 2024)
The development of human civilization with increasing population and needs for energy, food and comfort leads to the production of numerous air pollutants as products or by-products of energy production and industrial activities. Greenhouse gases is a major category of air pollutants with impacts on climate and ecosystem development. Atmospheric aerosols are also important with multiple impacts on climate, as well as human and ecosystem health. We here provide an insight into the sources, sinks and impacts of these air pollutants and their link to energy production. Targeting a carbon-free economic growth will contribute in mitigating air pollution by reducing these air pollutants and their undesirable effects. Trend analysis of air pollutant levels shows that clean air directives, implemented to protect human health and reduce acid rain, have been efficient in limiting air pollution by short-lived species, with mean atmospheric lifetimes less than a year. For greenhouse gases that have longer lifetimes in the atmosphere, i.e. decades or centuries and therefore long periods are required to reduce their atmospheric levels, immediate action is needed to support future sustainability.